Chronic treatment with glucocorticoids does not affect egg quality but increases cortisol deposition into egg albumen and elicits changes to the heterophil to lymphocyte ratio in a sex-dependent manner - Oluwagbenga, E. M.; Tetel, V.; Tonissen, S.; Karcher, D. M.; Fraley, G. S. (Frontiers in Physiology, 2023)
During chronic stress, there is an initial increase in glucocorticoid (GC) levels, but they then return to low, albeit not baseline, levels. Recent studies have renewed interest in cortisol in that it may also have important roles in the stress response. The purpose of our study was to test the hypothesis that chronic treatment with low levels of either corticosterone or cortisol would alter HLR and immune organ morphometrics. Further, we wanted to determine if chronic treatment with either GC would elicit an increase in cortisol levels in egg albumen. To test our hypotheses, we implanted silastic capsules that contained corticosterone, cortisol, or empty capsules as controls (N=5/sex/treatment). Blood serum, smears, body weights, and egg quality data were collected. Ducks were then euthanized and body weight, weights of spleens, livers, and the number of active follicles were recorded. Albumen GC levels were assessed using mass spectrometry. Data were analyzed using a 2- or 3-way ANOVA as appropriate and post hoc with Fishers PLSD. No treatment elicited differences in egg quality measures or body weight compared to controls. Corticosterone treatment did elicit an increase in serum corticosterone (p < 0.05), but not cortisol, levels compared to controls in both sexes. Both cortisol and corticosterone treatments increased (p < 0.05) serum levels of cortisol compared to controls. Relative spleen weights were higher (p < 0.05) in hens following corticosterone but not cortisol treatment. No other organs showed any differences among the treatment groups. Both GCs elicited an increase (p < 0.001) in HLR in hens at all time-points over the 2-week treatment period compared to controls. Cortisol, not corticosterone, only elicited an increase in HLR for drakes (p < 0.05) compared to controls but only at day 1 after implants. Chronic treatment with cortisol, but not corticosterone, elicited an increase (p < 0.01) in egg albumen cortisol levels compared to other groups. Corticosterone was not detected in any albumen samples. Our results suggest that glucocorticoids elicit differential effects and although corticosterone has been stated to be the predominant GC in avian species, cortisol may provide critical information to further understand bird welfare.